Incorporation of chitosan and glass substrate for improvement in adsorption, separation, and stability of TiO2 photodegradation - Amin, M.N.I.; Julkapli, N.M.; Hamid, Sharifah Bee Abd (Springer Verlag (Germany), 2016)
It is demonstrated that single titanium dioxide (TiO2) has high potential for photodegradation of pollutants. However, it is still far from becoming an effective photocatalyst system, due to issues of adsorption process, separation, as well as dissolution. Therefore, this study highlights the high adsorption capacity, simplified separation, and the promising stability of TiO2(SY) (synthesized via sol–gel method) photocatalyst, fabricated using chitosan–TiO2(SY) and supported by glass substrate (Cs–TiO2(SY)/glass substrate) photocatalysts. Chitosan (Cs), with abundant –R–NH and NH2 groups, promotes the adsorption sites of methyl orange (MO) and OH groups for major attachment to TiO2(SY). Meanwhile, the glass substrate increases stability and assists separation of the photocatalysts. Initially, nano-TiO2(SY) has been characterized using high-resolution transmission electron microscope. Cs–TiO2(SY)/glass substrate was fabricated via dip-coating. The distribution and interface between the photocatalytic components were characterized by Fourier transform infrared absorption spectroscopy, UV–Vis diffuse reflectance spectroscopy, field emission scanning electron microscopy, and energy-dispersive spectrometer. UV–Vis analysis of the multilayer photocatalyst (2, 4, 6, and 8 layers) was further carried out by the adsorption–photodegradation, with MO as model of pollutant. Seventy percent of the total removal of MO via optimized eight layers of photocatalyst was achieved within 1 h of UV irradiation. The adsorption photocatalyst achieved 50 % with no exposure to UV light for 15 min of irradiation. It is concluded that suitable photocatalytic conditions and sample parameters possessing the multilayer photocatalyst of Cs–TiO2(SY) are beneficial toward the adsorption–photodegradation process in wastewater treatment.